Investing online for dummies - Krantz, Matt (Wiley, 2010)
A hands-on, practical guide that shows you how to find an online broker, pick a winning strategy, and construct a successful portfolio.
Print version record
Keywords: Investments; Electronic trading of securities; Investissements; Valeurs mobilières; Commerce électronique; BUSINESS & ECONOMICS; Investments & Securities; General